Psicomotricidade: uma perspectiva psicopedagógica no desenvolvimento de crianças pequenas na escola - Silva, Aline de Sousa (2015)
This study presented a placement on the psychomotor and their contributions in early childhood education, analyzing the psycho contributions in cognitive, physical and emotional development of children. Therefore, it was necessary to run an interview with institutional psychologists to check their knowledge of the psychomotor and how it is inserted in schools in the learning process of young children. Based on this assumption, the survey counted on the collaboration of 3 female psychologists, aged 25 and 32, who work in schools in the private and public schools in the city of João Pessoa. For building this research, we used semi-structured interviews with five issues where the goal is to understand the design of educational psychologists about the practice of motor skills in nursery schools. Given the results, it was noticed that the psychomotor is used in preschools, where teachers often do not realize they are using it, but practice this habit with the educational psychologist, and can further improve the practice of psychomotor education for full development of children and helping in any difficulties that may arise. Therefore, the educational psychology and motor skills can be linked by building a different view regarding the human development and intervention with young children.